Rotational dephasing of a gold complex probed by anisotropic femtosecond x-ray solution scattering using an x-ray free-electron laser. (3rd November 2015) - Kim, Jong Goo; Kim, Kyung Hwan; Oang, Key Young; Kim, Tae Wu; Ki, Hosung; Jo, Junbeom; Kim, Jeongho; Sato, Tokushi; Nozawa, Shunsuke; Adachi, Shin-ichi; Ihee, Hyotcherl
Abstract: The orientational dynamics of a gold trimer complex in a solution are investigated by using anisotropic femtosecond x-ray solution scattering measured by an x-ray free-electron laser. A linearly polarized laser pulse preferentially excites molecules with transition dipoles oriented parallel to the laser polarization, leading to the transient alignment of excited molecules. Such photoselectively aligned molecules give rise to an anisotropic scattering pattern that has different profiles in parallel and perpendicular directions with respect to laser polarization. Anisotropic x-ray scattering patterns obtained from the transiently aligned molecules contain information on the molecular orientation. By monitoring the time evolution of the anisotropic scattering pattern, we probe the rotational dephasing dynamics of [Au(CN)2 − ]3 in a solution. We found that rotational dephasing of [Au(CN)2 − ]3 occurs with a time constant of 13 ± 4 ps. By contrast, time-resolved scattering data on FeCl3 in a water solution, which does not accompany any structural change and gives only the contributions of solvent heating, lacks any anisotropy in the scattering signal.